2019
DOI: 10.1039/c9cc04817k
|View full text |Cite
|
Sign up to set email alerts
|

Pd-catalyzed cascade reactions involving skipped dienes: from double carbopalladation to remote C–C cleavage

Abstract: A ligand-controlled Pd-catalyzed cascade relying in the control of two distinctive processes: oxidative addition to Pd(0) and isomerization of olefins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…After that, intermediate 38 participates in an uncommon β‐alkenyl rupture to generate complex 39 , and a 1,2‐migratory insertion affords structure 40 which can undergo a subsequent β‐H elimination process to end up in the synthesis of desired product 36 ( Scheme 6). [31] This reaction is a rare example of a β‐vinyl elimination which occurs from a quaternary carbon where no hydride elimination is possible.…”
Section: β‐Eliminations Cleaving C−c Bondsmentioning
confidence: 99%
“…After that, intermediate 38 participates in an uncommon β‐alkenyl rupture to generate complex 39 , and a 1,2‐migratory insertion affords structure 40 which can undergo a subsequent β‐H elimination process to end up in the synthesis of desired product 36 ( Scheme 6). [31] This reaction is a rare example of a β‐vinyl elimination which occurs from a quaternary carbon where no hydride elimination is possible.…”
Section: β‐Eliminations Cleaving C−c Bondsmentioning
confidence: 99%
“…Our group is interested in the study of cascade reactions involving the intramolecular carbopalladation of alkenes . Noteworthy, carbopalladation cascade reactions are not limited to the use of alkenes, they have also been successfully implemented in substrates bearing alkynyl fragments .…”
Section: Figurementioning
confidence: 99%
“…We reported recently a ligand‐controlled Pd‐catalyzed reaction taking place on 2‐haloarylethers bearing a 1,4‐diene tethered chain . We found that bulky monodentate ligands such as PCy 3 promoted a sequential double carbopalladation of the 1,4‐diene moiety, affording interesting [3.4]‐spirodihydrofuranes.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It is worth to mentioning that 4-exo-trig cyclization is rarely reported (Scheme 3). [10] The fully intramolecular double Heck cyclization has also been shown to be a powerful tool for the total synthesis of natural products containing congested quaternary carbon centers.…”
Section: Fully Intramolecular Double Heck Reactionmentioning
confidence: 99%